Mg2SnO4 ceramicsII. Electrical characterization - Azad, Abdul-Majeed; Min, Liew Jing; Alim, Mohammad A (Elsevier, 2001)
The inverse spinel-structured Mg2SnO4 possessing steady capacitance over the temperature range between 27 and 300°C in a frequency domain spanning nearly four decades has been examined by an a.c. technique. The samples investigated in this study were synthesized by using solid state reaction (SSR) and self-heat-sustained (SHS) techniques. The a.c. immittance (impedance or admittance) measurements in the frequency range 5 Hz-13 MHz were carried out on bodies sintered at 1500°C/6 h and 1600°C/2 h. The acquired electrical data exhibited relaxation in the Z*-plane alone, in the form of a small arc of a large semicircle. The magnitude of the terminal capacitance was found to be in a narrow window of ∼8-11 pF, while the average dielectric constant was about 10. Further analysis also revealed that this material system possessed ultra-low temperature coefficient of capacitance (TCC) and dielectric constant (TCK) along with very small magnitude of loss tangent.